2017
DOI: 10.3389/fimmu.2017.00191
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role of Salmonella Infection in the Onset of Inflammatory Bowel Diseases

Abstract: Inflammatory bowel disease (IBD) includes a set of pathologies that result from a deregulated immune response that may affect any portion of the gastrointestinal tract. The most prevalent and defined forms of IBD are Crohn’s disease and ulcerative colitis. Although the etiology of IBD is not well defined, it has been suggested that environmental and genetic factors contribute to disease development and that the interaction between these two factors can trigger the pathology. Diet, medication use, vitamin D sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 137 publications
(201 reference statements)
0
49
0
1
Order By: Relevance
“…Several viral pathogens have been associated with IBD (38)(39)(40)(41). Similarly, a number of bacterial pathogens, such as Salmonella and Campylobacter, have been linked to IBD (42)(43)(44). For example, adherent invasive Escherichia coli is commonly found in Crohn's disease patients with ileal involvement (45), whereas Yersinia enterocolitica has been associated with ulcerative colitis in adults (46).…”
Section: Discussionmentioning
confidence: 99%
“…Several viral pathogens have been associated with IBD (38)(39)(40)(41). Similarly, a number of bacterial pathogens, such as Salmonella and Campylobacter, have been linked to IBD (42)(43)(44). For example, adherent invasive Escherichia coli is commonly found in Crohn's disease patients with ileal involvement (45), whereas Yersinia enterocolitica has been associated with ulcerative colitis in adults (46).…”
Section: Discussionmentioning
confidence: 99%
“…Mesalazine inhibits the growth of Mycobacterium avium subspecies paratuberculosis, which has been reported to be intimately linked to the etiology of CD [76], in a dose-dependent manner in vitro [77]. Another study has reported that mesalazine downregulates the gene expression that is associated with bacterial invasiveness and antibiotic resistance in Salmonella enterica serovar Typhimurium [78], which could promote the onset of IBD after its infection [79,80]. Furthermore, mesalazine inhibits the growth of sulfate-reducing bacteria and suppresses sulfide production in IBD patients [81,82].…”
Section: The Effects Of Medication For Ibd On Gut Microbiotamentioning
confidence: 99%
“…In patients with IBD, the abundance of intestinal symbiotic microbiota decreased, and that deficiency led to decreased secretion of antimicrobial peptides (α‐defensins) from Paneth and Goblet cells and increased REGIIIγ (Schultz et al . 2017). Notably, IBD patients showed a reduction of some Firmicutes ( Faecalibacterium prausnitzii ; a butyrate‐producer), Verrucomicrobia ( Akkermansia muciniphila ; a propionate‐producer) and an increase of Proteobacteria (Mahalhal et al .…”
Section: Intestinal Diseasesmentioning
confidence: 99%
“…Activated macrophages produce pro‐inflammatory cytokines that overstimulate Th1 or Th17 cells, to induce inflammation (Schultz et al . 2017). The loss of intestinal barrier integrity leads to increased bacterial antigen translocation and stimulation of the inflammatory response of intestinal mucosa, which is the core pathological feature of IBD.…”
Section: Intestinal Diseasesmentioning
confidence: 99%